2000
DOI: 10.1021/bi0001527
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Dimerization, Binding, Stability, and Folding by Mutation of the Neurophysin Subunit Interface

Abstract: Bovine neurophysins, which have typically served as the paradigm for neurophysin behavior, are metastable in their disulfide-paired folded state and require ligand stabilization for efficient folding from the reduced state. Studies of unliganded porcine neurophysin (oxytocin-associated class) demonstrated that its dimerization constant is more than 90-fold greater than that of the corresponding bovine protein at neutral pH and showed that the increased dimerization constant is accompanied by an increase in sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(39 citation statements)
references
References 30 publications
0
39
0
Order By: Relevance
“…Numerous data suggest that the recognition and specificity require the directed forces of interaction such as hydrogen bonds and electrostatic forces, whereas the binding energy is probably also determined by hydrophobic forces [2,19,33,[43][44][45][46][47][48][49][50][51][52][53]. It is also suggested that the most binding energy is related only to several amino acids from the interface, so called "hot spots" [54][55][56][57].…”
Section: Thermodynamics and Kinetics Of Protein-protein Interactionsmentioning
confidence: 99%
“…Numerous data suggest that the recognition and specificity require the directed forces of interaction such as hydrogen bonds and electrostatic forces, whereas the binding energy is probably also determined by hydrophobic forces [2,19,33,[43][44][45][46][47][48][49][50][51][52][53]. It is also suggested that the most binding energy is related only to several amino acids from the interface, so called "hot spots" [54][55][56][57].…”
Section: Thermodynamics and Kinetics Of Protein-protein Interactionsmentioning
confidence: 99%
“…The preparation of recombinant WT mature BNP-I and oxytocin precursor and mutagenesis of wild type cDNA have been described previously (17,20). The recombinant mature mutant proteins in the present study were expressed in Escherichia coli, folded at pH 8.0 in the presence of ␤-mercaptoethanol and 10 mM Phe-Tyr-NH 2 , and purified by affinity chromatography as described for the recombinant mature WT protein (17). A large fraction of the protein so prepared is covalently damaged prior to folding (17,20), and the remaining protein folds with variable efficiency depending on its structure (see below).…”
Section: Preparation Of Wild Type and Recombinant Proteins-bnp-imentioning
confidence: 99%
“…The recombinant mature mutant proteins in the present study were expressed in Escherichia coli, folded at pH 8.0 in the presence of ␤-mercaptoethanol and 10 mM Phe-Tyr-NH 2 , and purified by affinity chromatography as described for the recombinant mature WT protein (17). A large fraction of the protein so prepared is covalently damaged prior to folding (17,20), and the remaining protein folds with variable efficiency depending on its structure (see below). The covalent structures of mutants were confirmed by DNA sequencing of the plasmids from which they were prepared and by mass spectrometry.…”
Section: Preparation Of Wild Type and Recombinant Proteins-bnp-imentioning
confidence: 99%
See 2 more Smart Citations